Association between depressive symptom clusters and food attentional bias. (December 2018) - Hawkins, Misty A.W.; Vrany, Elizabeth A.; Cyders, Melissa A.; Ciciolla, Lucia; Wells, Tony T.; Stewart, Jesse C.
Abstract: Background: The mechanisms underlying the depression-obesity relationship are unclear. Food attentional bias (FAB) represents one candidate mechanism that has not been examined. We evaluated the hypothesis that greater depressive symptoms are associated with increased FAB. Method: Participants were 89 normal weight or overweight adults (mean age = 21.2 ± 4.0 years, 53% female, 33% non-white, mean body mass index in kg/m 2  = 21.9 ± 1.8 for normal weight; 27.2 ± 1.5 for overweight). Total, somatic, and cognitive-affective depressive symptom scores were computed from the Patient Health Questionnaire-8 (PHQ-8). FAB scores were calculated using reaction times (RT) and eye-tracking (ET) direction and duration measures for a food visual probe task. Age, gender, race/ethnicity, and body fat percent were covariates. Results: Only PHQ-8 somatic symptoms were positively associated with RT-measured FAB ( β  = 0.23, p  = .04). The relationship between somatic symptoms and ET direction ( β  = 0.18, p  = .17) and duration ( β  = 0.23, p  = .08) FAB indices were of similar magnitude but were not significant. Somatic symptoms accounted for 5% of the variance in RT-measured FAB. PHQ-8 total and cognitive-affective symptoms were unrelated to all FAB indices ( p s ≥ 0.09). Conclusions: Only greater somatic symptoms of depression were linked to food attentional bias as measured using reaction time. Well-powered prospective studies should examine whether this bias replicates, particularly for eye-tracking measures, and whether it partially mediates the depression-to-obesity relationship. Highlights: Depression may lead to obesity via increased attention to and intake of food. Greater somatic depressive symptoms were linked to greater food attentional bias measured using reaction time. Food bias may ultimately result in increased calorie intake in depression.